Deep Vein Thrombosis and Diabetes Mellitus Type 2 as Complications of Psoriatic Arthritis: A Case Report - Hersih Srinowati; Lita Diah Rahmawati (Indian Journal of Forensic Medicine & Toxicology, 2022)
A woman, 45 years old, complained of low back pain that improves with activity or analgesic andreoccurs when resting. The patient also complained of swollen joints, fever, shortness of breath, flakyskin and fragile nails. Physical examination found multiple inflamed joints, thickened and fragilenails, fever, limited range of movement of knee and ankle and positive Homan sign. Workup foundnegative anti-rheumatoid factor, increased blood sugar level, increased erythrocyte sedimentation rate,increased C-reactive protein, bacteria in urine, increased D-dimer, and imaging of lumbar spondylosisand sacroiliitis, and deep vein thrombosis in the left inferior limb using Doppler ultrasonography. Thepatient was diagnosed as psoriatic arthritis, deep vein thrombosis, type 2 diabetes mellitus, and urinarytract infection. The patient was given sulfasalazin, fondaparinux, warfarin, insulin, and antibiotic. Onthe 15th day of treatment, the patient experienced sudden shortness of breath and chest pain. The patientdied due to suspected cardiovascular event.